A Crosslinked Polyethyleneglycol Solid Electrolyte Dissolving Lithium Bis(trifluoromethylsulfonyl)imide for Rechargeable Lithium Batteries. Issue 20 (24th September 2019) - Tian, Guiying; Zhao, Zijian; Zinkevich, Tatiana; Elies, Katharina; Scheiba, Frieder; Ehrenberg, Helmut
Abstract: Replacing liquid electrolytes with solid ones can provide advantages in safety, and all‐solid‐state batteries with solid electrolytes are proposed to solve the issue of the formation of lithium dendrites. In this study, a crosslinked polymer composite solid electrolyte was presented, which enabled the construction of lithium batteries with outstanding electrochemical behavior over long‐term cycling. The crosslinked polymeric host was synthesized through polymerization of the terminal amines of O, O‐bis(2‐aminopropyl) polypropylene glycol‐ block ‐polyethylene glycol‐ block ‐polypropylene glycol and terminal epoxy groups of bisphenol A diglycidyl ether at 90 °C and provided an amorphous matrix for Li + dissolution. This composite solid electrolyte containing Li + salt and garnet filler exhibited high flexibility, which supported the formation of favorable interfaces with the active materials, and possessed enough mechanical strength to suppress the penetration of lithium dendrites. Ionic conductivities higher than 5.0×10 −4  S cm −1 above 45 °C were obtained as well as a wide electrochemical stability window (>4.51 V vs. Li/Li + ) and a high Li + diffusion coefficient (≈16.6×10 −13  m 2  s −1 ). High cycling stability (>500 cycles or 1000 h) was demonstrated. Abstract : Crosslinked lovers ! A crosslinked polyethyleneglycol‐based composite solid electrolyte with lithium lanthanum zirconate filler delivers high ionic conductivity and good wettability of the electrode surface. Ionic conductivities higher than 5.0×10 −4  S cm −1 are obtained as well as a wide electrochemical stability window (>4.51 V vs. Li/Li + ) and a high Li + diffusion coefficient (≈16.6×10 −13  m 2  s −1 ).